Association of TBX21 gene polymorphisms and acute anterior uveitis risk in a Chinese population: A case-control study. (April 2023) - Shan, Jiankang; Li, Lin; Du, Liping; Yang, Peizeng
Abstract: Copy number variations (CNVs) in TBX21 gene have been reported to be significantly and positively correlated with acute anterior uveitis (AAU). Our study was performed to further determine whether single nucleotide polymorphisms (SNPs) in TBX21 gene confer susceptibility to AAU in a Chinese population. In our case-control study, 420 AAU patients and 918 healthy controls were included. SNP genotyping was conducted via the MassARRAY™ iPLEX Gold platform. Association and haplotype analyses were performed via SPSS 23.0 and SHEsis software. No significant association was observed between two candidate SNPs of TBX21 gene (rs4794067, rs11657479) and susceptibility to AAU ( P c > 0.05). In stratification analysis, the result also showed no significant difference between the HLA-B27 positive AAU patients and non-typed healthy controls. Additionally, no association was detected between TBX21 haplotypes and AAU risk. In conclusion, the polymorphisms rs4794067 and rs11657479 in TBX21 gene did not confer disease susceptibility to AAU in a Chinese population. Highlights: First association analysis of TBX21 gene SNPs in AAU patients. Allele and genotype distributions of SNPs were compared under different inheritance models. TBX21 gene polymorphisms did not confer disease susceptibility to AAU in a Chinese population.